(untitled) (Journal of Nepal Geological Society, 2000)
In the Adriatic region of central Italy, there are many mineralised (salt and sulphureous) springs, often used for therapeutic purposes. The hydrogeological characteristics of the springs and their tectonic set-up are examined in this paper. The salt springs generally emerge from the Plio-Pleistocene and Messinian deposits. The waters emerging from the Messinian deposits originate from marine waters subjected to evaporation. This leads to the precipitation of gypsum and formation of brines isolated by clayey deposits. Even the salt waters emerging from the Plio-Pleistocene deposits originate from marine waters trapped in the arenaceous Pliocene deposits. The waters are subjected to an ultra-filtration process through the clayey membrane with the formation of brines. The study reveals that the springs are located in the main thrust fronts, and the springs with higher salinity emerge in the thrusts that squeezed out the brine waters from the post-orogenic Plio-Pleistocene sequence. The sulphureous springs emerge from the Messinian and Plio-Pleistocene deposits and from the Apennine Meso-Cenozoic limestone ridges. The sulphureous springs emerging from the terrigenous sequence are connected with the Messinian evaporites, while the sulphureous springs emerging from the limestone ridges are related to the Messinian and Triassic evaporite deposits of the Umbrian-Marchean sequence. In the emergence zones of the salt waters, typical mud volcanoes or puddles are present due to suspended mud in the waters. Generally, the sulphureous springs emerge along streams whose waters are whitish and emit the typical smell because of sulphur precipitation.